Politics and Ethics in Farabi’s View (Raparin Journal of Humanities (RJH), 2024)
Farabi, the great philosopher and founder of Islamic philosophy, has a comprehensive global political system for managing humanity entitled the city of Fazila. The city of Fazila is a city that is perfect in all aspects and contrary to the cities of non-fazila and leads us towards eternal happiness. The people of Fazila are working hand in hand for happiness. Farabi, taking advantage of Islam and ancient Greek philosophy, establishes a strong political system in which he believes that morality and politics bind an inseparable relationship. This means that the essence of politics reaches virtue within the framework of morality and the commitment of the people of Fazila a city to high morals. The ruler and the country's president are very important to Farabi. It is an important source of policy implementation and the high principles of The City of Fazila and provides happiness for its people. The ruler has qualities such as psychological, physical, and wisdom that distinguish him from all the people of the city and provide him with the ability to take responsibility for the country. In this way, Farabi establishes the theory of the Islamic State as a Muslim philosopher, and despite taking advantage of old Greek philosophy, especially philosophers such as Plato and Aristotle, it opens the time for the realization and preservation of a set of established Islamic principles, such as believing in God, the messenger and the angels, the existence of inspiration and the revelation of God, and knowing the psyche and the universe in his Islamic state. In terms of education, politics, morality and division of the community classes, and the characteristics of the city's president and ruler (Shahfailasuf), there are common and different points between Farabi and Plato. Comparing the views of the two philosophers helps to understand Farabi's views in Fazila and the theory of his Islamic state in general, and Farabi's view of politics and ethics in particular.